WEWENANG PEMERINTAH DIBIDANG PEMBINAAN NOTARIS DI JAWA TIMUR - Aulia, Farihan (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2018)
Functions  and  responsibilities of notary as  public official, always  have deals by law aspect. Notary must be give explain and  testimony a content deed. In reality more  mistake happen  effect from  notary negligence and effect from  high value lobbying  , now   rarely happen. Tehe problem take from effect from impelementation of constitution no 2 Years 2014 by government, with law effect to   law of notary  and obstacles solution  implementation  controlling to  notary. Aim of this research  describe and analys   uthority,  government position to  coach asa regulator stand for  valid of  constitution especially in east java area. Controlling not only done bya  notary association buat also done  by  Minister  of Law and Human Right.  Initially  based on  constitution No,30 Years 2014 about notary occupation . After than have delegate to  supervisory board and coaching  , after that changed to constitution  No . 2 years 2014  chapter 66 A, Law and human Right regulatory no M.02 PR.08. 10 years 2004, constitution of notary occupation give bordering authorized  responsibility and prohibition which must be obey to as a notary. About this arranged in  chapter 15,16, 17 and ethic  profession of notary have controloed by   supervisory board  as regulated on chapter 67,68, 69 constituation No.30 years 2004.  Step by step  must be done  by supervisory  on handle  control of  obstacles  and to coach notary as such as : a. supervisory board as MPD,MPN,MPW to hold on  the  job not alal have synergy, all this can do by to held  law anylises  seminar together and  law workshop together.